2009
DOI: 10.1098/rspb.2009.1134
|View full text |Cite
|
Sign up to set email alerts
|

Human odometer is gait-symmetry specific

Abstract: In 1709, Berkeley hypothesized of the human that distance is measurable by 'the motion of his body, which is perceivable by touch'. To be sufficiently general and reliable, Berkeley's hypothesis must imply that distance measured by legged locomotion approximates actual distance, with the measure invariant to gait, speed and number of steps. We studied blindfolded human participants in a task in which they travelled by legged locomotion from a fixed starting point A to a variable terminus B, and then reproduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 21 publications
5
46
0
Order By: Relevance
“…For experimental distances of 7.6, 15.2, and 22.9 m, Turvey et al (2009) confirmed Schwartz's (1999 finding that walk-walk and run-walk were equivalent M − R conditions (see also Isenhower et al 2012), but showed that it was a special case. They did so by manipulating the symmetry classes of bipedal gaits identified by Pinto and Golubitsky (2006).…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…For experimental distances of 7.6, 15.2, and 22.9 m, Turvey et al (2009) confirmed Schwartz's (1999 finding that walk-walk and run-walk were equivalent M − R conditions (see also Isenhower et al 2012), but showed that it was a special case. They did so by manipulating the symmetry classes of bipedal gaits identified by Pinto and Golubitsky (2006).…”
Section: Introductionsupporting
confidence: 69%
“…In the laboratory, the measure M and the report R can both be conducted without benefit of vision. When so conducted, experiments (e.g., Isenhower et al 2012;Turvey et al 2009Turvey et al , 2012 suggest that M and R should be conceived as two components of a single system. Here we present an axiomatic basis for deriving the model of the M − R system developed heuristically in Turvey et al (2012).…”
Section: Axiomatic Approach To M − R System Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the same behaviors can be achieved adaptively by a family of systems of interacting components. Recently, based on the same classification approach, Turvey et al (2009) have shown that the way we measure distance by the use of our locomotor motion is determined by gait symmetry. Interestingly, Marey (1873) analyzed the coordination between two humans walking one closely following the other, and found that the single animal quadruped gaits are spontaneously adopted (see also Harrison and Richardson, 2009), hence the vast ensemble of group theoretic predictions for quadrupeds could be tested in a dyadic scheme in future experiments.…”
Section: The Case For Topological Equivalencementioning
confidence: 99%